Phosphorus (P) for Citrus Trees - Mongi Zekri; Tom Obreza (EDIS)
Phosphorus deficiency is not common in Florida citrus groves. If it does occur, it is more difficult to diagnose than nitrogen (N) deficiency or other nutrient element deficiencies. Growth is reduced when P supply is too low. Phosphorus is highly mobile in plants, so when it is deficient, it may move from old leaves to young leaves and other actively growing areas where energy is needed to form seeds and fruit. This 4-page fact sheet was written by Mongi Zekri and Tom Obreza and published by the UF Department of Soil and Water Science, July 2013.